Emergent models of sport development and delivery: The case of triathlon in Australia and the US - Pillips, P.; Nwland, B. (Sport Management Review, 2014)
Sport development is a core concern for all nations as they seek to enhance elite performance and cultivate opportunities for mass participation. In the sport of triathlon, new models for sport development have been shown to exist where third party organisations have a critical role in the delivery of it. Using institutional theory as a framework, the purpose of this study was to explore the emerging models of sport development in triathlon. A case study of triathlon in Australia and in the United States was used. The results illustrated emerging models of sport development in both the US and Australia. Third party organisations as well as local councils have become increasingly involved in the creation and implementation of programmes and activities that would normally be the responsibility of a governing body. As such, the organisational fields and institutional logics in triathlon are rendering governing bodies irrelevant. Governing bodies are grappling with finding relevance and legitimacy in triathlon. Implications for sport management research, practice, and education are discussed.